Formate, acetate, and propionate as substrates for sulfate reduction in sub-arctic sediments of Southwest Greenland - Glombitza, Clemens; Jaussi, Marion; Røy, Hans; Seidenkrantz, Marit-Solveig; Lomstein, Bente A.; Jørgensen, Bo B. (Frontiers in Microbiology, 2015)
Volatile fatty acids (VFAs) are key intermediates in the anaerobic mineralization of organic matter in marine sediments. We studied the role of VFAs in the carbon and energy turnover in the sulfate reduction zone of sediments from the sub-arctic Godthåbsfjord (SW Greenland) and the adjacent continental shelf in the NE Labrador Sea. VFA porewater concentrations were measured by a new two-dimensional ion chromatography-mass spectrometry method that enabled the direct analysis of VFAs without sample pretreatment. VFA concentrations were low and surprisingly constant (4-6 µmol L-1 for formate and acetate, and 0.5 µmol L-1 for propionate) throughout the sulfate reduction zone. Hence, VFAs are turned over while maintaining a stable concentration that is suggested to be under a strong microbial control. Estimated mean diffusion times of acetate between neighboring cells were <1 second, whereas VFA turnover times increased from several hours at the sediment surface to several years at the bottom of the sulfate reduction zone. Thus, diffusion was not limiting the VFA turnover. Despite constant VFA concentrations, the Gibbs energies (Gr) of VFA-dependent sulfate reduction decreased downcore, from -28 to -16 kJ (mol formate)-1, -68 to -31 kJ (mol acetate)-1, and -124 to -65 kJ (mol propionate)-1. Thus, Gr is